Contribution to the feeding ecology of the banded puffer fish Colomesus psittacus (Tetraodontidae) in north Brazilian mangrove creeks - U. Krumme; H. Keuthen; U. Saint-Paul; W. Villwock (Brazilian Journal of Biology)
Stomach contents were examined from 102 banded puffer, Colomesus psittacus (Tetraodontidae), caught from intertidal mangrove creeks at diurnal neap tides between June and September, 1997 (early dry season) near Bragança (north Brazil). The study found that C. psittacus were specialized predators of Cirripedia (Balanus spp.) and Brachyuran crabs (Uca spp., Pachygrapsus gracilis) (mean: 58 and 38% by dry weight, respectively), emphasizing a short food chain in the mangrove system. Cirripedia and Brachyura dominated the diet in all size classes, however, the prey spectrum narrowed with fish size. The mean daily consumption of Cirripedia and Brachyura was 6.2% body weight of C. psittacus. On average C. psittacus consumed 100.3 g.ha-1.d-1 of Cirripedia and 178.7 g.ha-1.d-1 of Brachyura (wet weight). The predation on Brachyuran crabs - a significant driver of fluxes of organic matter and energy in the system - provides C. psittacus with an important ecological function in the mangrove food web. A plant-animal interaction is proposed where C. psittacus exerts a mutually beneficial cleaning function on the Aufwuchs (Cirripedia and associated epibiota) of Rhizophora mangle stilt roots. Our results and those of other studies suggest that C. psittacus encounter optimum foraging conditions in the mangrove at high inundations at daylight (spring tide-day) whereas darkness and low inundations are linked to poor foraging conditions (neap tide-night). The C. psittacus resource could be used as an alternative income in the region in terms of i) sustainable catch and filet processing for exports to East Asia, ii) developing certified aquaculture methods for breeding puffers for the aquarium trade.